Plant Frataxin in Metal Metabolism - Gomez-Casati, Diego F.; Busi, Maria V.; Pagani, Maria A. (Frontiers in Plant Science, 2018)
Frataxin is a highly-conserved protein from prokaryotes to eukaryotes. Several functions related to iron metabolism have been postulated for this protein, including Fe-S cluster and heme synthesis, response to oxidative damage and oxidative phosphorylation. In plants, the presence of one or two isoforms of this protein with dual localization in mitochondria and chloroplasts has been reported. Frataxin deficiency affects iron metabolism in both organelles, leading to an impairment of mitochondrial respiration, and chlorophyll and photosynthetic electron transport deficiency in chloroplasts. In addition, plant frataxins can react with Cu2+ ions and dimerize, which causes the reduction of free Cu ions. This could provide an additional defense mechanism against the oxidation of Fe-S groups by Cu ions. While there is a consensus on the involvement of frataxin in iron homeostasis in most organisms, the interaction of plant frataxins with Cu ions, the presence of different isoforms, and/or the localization in two plant organelles suggest that this protein might have additional functions in vegetal tissues.